ILLEGAL ACTIONS OF NARCOTIC DRUGS OR PSYCHOTROPIC SUBSTANCES THE OBJECTIVE SIDE OF THE SPREAD THE VALUE OF THE QUALIFICATION OF THE CRIME (Journal of actual problems of jurisprudence, 2019)
This article discusses the importance of the objective side of the illicit distribution of narcotic and psychotropic substances in thequalifications of the staff.